(untitled) (Annals of Medical Research, 2021)
Aim: The purpose of this study was to determine the effects of using a bag-valve-mask (BVM) or endotracheal intubation (EI), and administering epinephrine during the transfer of Out-of-hospital Cardiac Arrests (OHCA) cases, and to show the effects of BVM or EI, and epinephrine use on discharge from the hospital and patient survival.Material and Methods: Totally 109 OHCA patients were included in the study. Group 1 included patients in whom return of spontaneous circulation was achieved after Cardiopulmonary resuscitation (CPR) and who were then discharged from the hospital within 30 days. Group 2 included patients who died after emergency CPR or hospitalization. A Student’s t-test was used for normally distributed continuous values, and a Chi-square (χ2) test was used for numerical data.Results: Sixteen (14.7%) of the OHCA cases survived and were discharged within 30 days, and 93 (85.3%) died. The outcomes were similar between those who received endotracheal intubation (EI) and BVM during hospital transfer (p = 0.569). Epinephrine was administered to 15 (19.2%) patients in group 2 and 5 (45.4%) patients in group 1 during the transfer period, but this difference was not significant (p = 0.167). Logistic regression modelling did not find an association between type of airway management, epinephrine use and 30-day discharge survival. Conclusion: The results of this study show that epinephrine had no effect on patient survival or hospital discharge in OHCA patients. Additionally, the effects of EI and BVM on 30-day survival and hospital discharge were similar.